Elastin-Like Recombinamer Hydrogels for Improved Skeletal Muscle Healing Through Modulation of Macrophage Polarization - Ibáñez-Fonseca, Arturo; Santiago Maniega, Silvia; Gorbenko del Blanco, Darya; Catalán Bernardos, Benedicta; Vega Castrillo, Aurelio; Álvarez Barcia, Ángel José; Alonso, Matilde; Aguado, Héctor J.; Rodríguez-Cabello, José Carlos (Frontiers in Bioengineering and Biotechnology, 2020)
Large skeletal muscle injuries, such as a volumetric muscle loss (VML), often result in an incomplete regeneration due to the formation of a non-contractile fibrotic scar tissue. This is, in part, due to the outbreak of an inflammatory response, which is not resolved over time, meaning that type-1 macrophages (M1, pro-inflammatory) involved in the initial stages of the process are not replaced by pro-regenerative type-2 macrophages (M2). Therefore, biomaterials that promote the shift from M1 to M2 are needed to achieve optimal regeneration in VML injuries. In this work, we used elastin-like recombinamers (ELRs) as biomaterials for the formation of non- (physical) and covalently (chemical) crosslinked bioactive and biodegradable hydrogels to fill the VML created in the tibialis anterior (TA) muscles of rats. These hydrogels promoted a higher infiltration of M2 within the site of injury in comparison to the non-treated control after 2 weeks (p<0.0001), indicating that the inflammatory response resolves faster in the presence of both types of ELR-based hydrogels. Moreover, there were not significant differences in the amount of collagen deposition between the samples treated with the chemical ELR hydrogel at 2 and 5 weeks, and this same result was found upon comparison of these samples with healthy tissue after 5 weeks, which implies that this treatment prevents fibrosis. The macrophage modulation also translated into the formation of myofibers that were morphologically more similar to those present in healthy muscle. Altogether, these results highlight that ELR hydrogels provide a friendly niche for infiltrating cells that biodegrades over time, leaving space to new muscle tissue. In addition, they orchestrate the shift of macrophage population toward M2, which resulted in the prevention of fibrosis in the case of the chemical hydrogel treatment and in a more healthy-like myofiber phenotype for both types of hydrogels. Further studies should focus in the assessment of the regeneration of skeletal muscle in larger animal models, where a more critical defect can be created and additional methods can be used to evaluate the functional recovery of skeletal muscle.